(Non-)mandatory nature and evidentiary value of DNA analysis in maternity and paternity proceedings: Jurisprudence of the European Court of Human Rights - Nedeljković, Natalija (Glasnik Advokatske komore Vojvodine, 2026)
The European Court of Human Rights consistently recognizes the right to know one’s biological origin as an integral element of the right to respect for private and family life, as well as the internationally recognized child’s right to identity. Contracting States to the European Convention on Human Rights have a positive obligation to ensure a fair balance between the child’s right to know their origin, on the one hand, and the putative parent’s right to respect for private life and physical integrity, or the existing legal parents’ right to preserve the stability of family relations, on the other hand. In this paper, the author examines the scope and evidentiary value of DNA analysis, while addressing broader socio-ethical issues – whether DNA analysis can or should be mandatory, the consequences of non-compliance, and whether the legal system provides alternatives to refusal. This research aims to synthesize the key standards in this field through a theoretical and empirical analysis of the Court’s case law. The author employed the following methods in the paper: the normative-dogmatic method, the comparative law method, content analysis, the case study method, and purposive sampling.